(untitled) (Krakowskie Pismo Kresowe, 2025)
“ZA DUŻO, BY UMRZEĆ, ZA MAŁO, BY WYŻYĆ”: THE FUNCTIONING OF CHEAP/FREE CANTEENS IN LVIV IN 1914-1915 The article examines the issue of free and cheap canteens in Lviv during the Russian occupation. It analyses the dynamics of their increasing number. Initially, cheap canteens were established primarily for the families of men enlisted in the Polish Legion of the Austro-Hungarian army. After Lviv was captured on 3 September 1914, the city authorities reali sed that the network of canteens for the general population needed to be expanded, as many residents had lost their regular income following the evacuation of Austrian government offices. Lviv was considered a “showcase of the Russian occupation,” and therefore the occupation authorities were actively involved in providing funds and provisions for the operation of city canteens. The city’s vice president, Tadeusz Rutowski, coordinated with the occupation administration, which enabled him to cover most of the canteens’ financial and food requirements.